Pelatihan Pembuatan Biskuit Ikan Patin Tempe dan Pembentukan Kader Usaha Mandiri Makanan Bergizi pada Ibu-Ibu PKK dalam mengatasi Stunting di Desa Petajen - Aisah, Aisah; Fatmawati, Tina Yuli; Armina, Armina (Universitas Baiturrahim, 2025)
Stunting is a growth and development disorder in children due to chronic malnutrition and repeated infections, characterized by a length or height below the standard. Based on an initial survey conducted in Petajen village, there were 55 toddlers experiencing nutritional problems of wasting and stunting. Lack of knowledge regarding diverse food consumption is one indicator of the cause of nutritional problems in toddlers in Petajen village. The potential of local resources such as catfish and tempeh is quite abundant, but has not been utilized optimally to increase the added value of food products. The purpose of this activity is to provide nutritious food education to PKK mothers through counseling and the formation of independent nutritious food cadres. The method used in this community service is training and mentoring in making catfish and tempeh biscuits. The result of this activity is biscuits made from catfish and tempeh which are expected to be one of the nutritious food choices to overcome nutritional problems and encourage community self-reliance for initial small-scale production. Based on the results of the implementation of Community-Based Empowerment, the characteristics of respondents are known that of the 11 respondents, the majority are in late adulthood (45.4%), some respondents have a high school education (54.5%). There was a very significant increase in knowledge after the training was given. Before the training, the average correct answer of participants was only 33.3%. After the training, the average correct answer increased to 87.5%, which reflects a 54.2% increase in knowledge. The formation of a Household-Based Small Business Group, training participants formed a small group that agreed to continue the production of patin fish biscuits and tempeh as a local superior product. This group began to design simple marketing strategies, such as sales in the surrounding environment, integrated health posts (posyandu), and village activities